Selection of The Chemical Composition of Steels and Their Thermal Hardening Mode Using A Computer Program - D. M. BERDIEV; М. А. UМАRОVА; T. N. IBODULLAEV (Research Parks Publishing LLC, 2023)
The relationships between the parameters of the structure of heat-treated steels and their abrasive wear resistance are established. At all temperatures of the final tempering of hardened steel, there is a direct relationship between its structure parameters and wear resistance when sliding friction against loose abrasive particles.